Pengembangan LKPD berbasis inkuiri pada materi aritmatika sosial untuk peserta didik Kelas VII - Wisnu Siwi Satiti; Arina Hidayati; M Qoyum Zuhriawan (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2023)
The concept of social arithmetic is widely applied in various real life contexts. However, many students experience difficulties in learning and understanding the concept of social arithmetic. This is because learning in class generally focuses on memorizing formulas and does not involve students building their understanding independently. In general, mathematics activities are also presented in routine problems in which the students operate the numbers listed in the questions into mathematical formulas. Therefore it is necessary to apply a learning that encourage students to involve actively and to think critically and analytically in learning, so that they are able to build their understanding independently. In addition, learning resources are also needed to present mathematical activities based on real-life contexts and facilitate student centered learning. Learning model that is relevant for achieving this goal is inquiry-based learning, and learning resources that can be used are Student Worksheets (LKPD). Therefore this study aims to produce valid and practical inquiry-based worksheets on concept of social arithmetic for seventh grade students. This study is a Research and Development (RD) study and applies ADDIE model which consists of 5 stages: analysis, design, development, implementation, and evaluation. The results show that the LKPD meet valid and practical criteria, and the results of the learning tests show that the LKPD has a potential effect on conceptual understanding skills and could be used in learning.